Boogsie, Jit in the Lead - Blood, Peter Ray (Sunday Express)
Arrangers Boogsie Sharpe and Jit Samaroo are enjoying remarkable success in this year's Panorama competition. Boogsie stands a good chance of having five steelbands in the national finals and Samaroo has three bands in the semi-finals.
Keywords: Arrangers (Musicians) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Competitions -- Trinidad and Tobago